2017
DOI: 10.1175/jcli-d-16-0285.1
|View full text |Cite
|
Sign up to set email alerts
|

Latent Heat Flux Sensitivity to Sea Surface Temperature: Regional Perspectives

Abstract: A global analysis of latent heat flux (LHF) sensitivity to sea surface temperature (SST) is performed, with focus on the tropics and the north Indian Ocean (NIO). Sensitivity of LHF state variables (surface wind speed Ws and vertical humidity gradients Δq) to SST give rise to mutually interacting dynamical (Ws driven) and thermodynamical (Δq driven) coupled feedbacks. Generally, LHF sensitivity to SST is pronounced over tropics where SST increase causes Ws (Δq) changes, resulting in a maximum decrease (increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…As the sensible heat flux is proportional to the difference of temperature between the surface air temperature and the sea surface temperature, variations of the surface temperature across the front have been taken into account in the AROME estimates of the sensible heat flux by rescaling it with the measured surface temperature. In the latent heat flux, we neglect the influence of variations of the surface temperature, which is less than 4 W m −2 around the Svalbard region (Kumar et al, ).…”
Section: Datamentioning
confidence: 99%
“…As the sensible heat flux is proportional to the difference of temperature between the surface air temperature and the sea surface temperature, variations of the surface temperature across the front have been taken into account in the AROME estimates of the sensible heat flux by rescaling it with the measured surface temperature. In the latent heat flux, we neglect the influence of variations of the surface temperature, which is less than 4 W m −2 around the Svalbard region (Kumar et al, ).…”
Section: Datamentioning
confidence: 99%
“…Additionally, Kumar et al (2017) found that the winds are always originated at sea in tropical regions. The authors also pointed out that large-scale winds blow from regions with cold SST towards regions with warmer SST and, therefore, the surface air is more humid and colder than SST.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a good SST representation with the models is important. Performing a global analysis of the LHF sensitivity to variations in SST focused on tropical regions, Kumar et al (2017) have found that the sensitivity of variables related directly to LHF (WIND and Q) and SST give rise to dynamic (WIND) and thermodynamic (Q)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the high correlation between SST and ocean LHF [51,52], we decided to maintain the high spatial resolution of SST4 dataset to increase spatial heterogeneity. To generate the monthly global ocean LHF products from 2003 to 2007, we used the bilinear interpolation method to interpolate other monthly input data (U, T a , q) to 4 km spatial resolution over 2003-2007.…”
Section: Satellite and Reanalysis Inputs To The Lhf Modelmentioning
confidence: 99%